Time-resolved Brownian tomography of single nanocrystals in liquid during oxidative etching - Sungsu Kang; Joodeok Kim; Sungin Kim; Hoje Chun; Junyoung Heo; Cyril F. Reboul; Rubén Meana-Pañeda; Cong T. S. Van; Hyesung Choi; Yunseo Lee; Jinho Rhee; Minyoung Lee; et al. (Nature Communications)
Abstract Colloidal nanocrystals inherently undergo structural changes during chemical reactions. The robust structure-property relationships, originating from their nanoscale dimensions, underscore the significance of comprehending the dynamic structural behavior of nanocrystals in reactive chemical media. Moreover, the complexity and heterogeneity inherent in their atomic structures require tracking of structural transitions in individual nanocrystals at three-dimensional (3D) atomic resolution. In this study, we introduce the method of time-resolved Brownian tomography to investigate the temporal evolution of the 3D atomic structures of individual nanocrystals in solution. The methodology is applied to examine the atomic-level structural transformations of Pt nanocrystals during oxidative etching. The time-resolved 3D atomic maps reveal the structural evolution of dissolving Pt nanocrystals, transitioning from a crystalline to a disordered structure. Our study demonstrates the emergence of a phase at the nanometer length scale that has received less attention in bulk thermodynamics.